PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Tiffani, Tiffani; Basri, Yesi Mutia; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aims of this research are to examine: The effect of profitability and leverage to firm value with corporate social responsibility as a moderating variable. The population of this research is the companies that listed in the Indonesian Stock Exchange in the period of 2012-2015. By using purposive sampling there are 24 companies that fulfil the criterias. The research data was analyzed by using simple regression analysis and multiple regression analysis with SPSS version 17.0. Based on the result, it can be concluded that; (1) profitability has the effect on firm value with a t-value of 3,125, t-table of 1,986, a significant 0,002; (2) leverage has the effect on firm value with a t-value of 2,614, t-table of 1,986, a significant 0,01. (3) corporate social responsibility as a moderating variable be able to influence profitability on firm value with t-value of 2,047, t-table of 1,986, a significant 0,044. (4) corporate social responsibility as a moderating variable not able to influence leverage on firm value with t-value of 1,746, t-table of 1,986, a significant 0,084.Keywords: Profitability, Leverage, Corporate Social Responsibility and firm value.